2021
DOI: 10.3390/v14010031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Male Reproductive Organs in the Transmission of African Swine Fever—Implications for Transmission

Abstract: African swine fever (ASF) has evolved from an exotic animal disease to a threat to global pig production. An important avenue for the wide-spread transmission of animal diseases is their dissemination through boar semen used for artificial insemination. In this context, we investigated the role of male reproductive organs in the transmission of ASF. Mature domestic boars and adolescent wild boars, inoculated with different ASF virus strains, were investigated by means of virological and pathological methods. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
2
12
1
1
Order By: Relevance
“…Previous studies indicated that ASFV did not enter live spermatozoa of spiked boar semen [13], but simultaneous entry of virus and spermatozoa into the ovum cannot be refuted at this point. Attachment of virions to molecules on spermatozoa has been formerly described for other DNA viruses, such as human papilloma virus (HPV, [37]).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies indicated that ASFV did not enter live spermatozoa of spiked boar semen [13], but simultaneous entry of virus and spermatozoa into the ovum cannot be refuted at this point. Attachment of virions to molecules on spermatozoa has been formerly described for other DNA viruses, such as human papilloma virus (HPV, [37]).…”
Section: Discussionmentioning
confidence: 88%
“…(2021) supported this hypothesis by confirming the presence of both viral genome and infectious virions in gonadal tissue of swine infected with ASFV strains of various genotypes (gt). In these studies, ASFV genome and infectious virions were detected in testes from sexually mature domestic pigs inoculated with Zambian ASFV isolates 'KAB 6/2' (gt XI) and 'SUM 14/11' (gt XIII) [13]. Studies with adolescent wild boar produced similar results for ASFV strains 'Belgium 2018/1' (gt II) and 'Germany 2020' (gt II) [13,14].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, in line with macroscopic findings, histopathology confirmed the severe course of disease in all animals regardless of the outbreak area and the virus variant. Since most wild boar studies focus only on macroscopic pathology, it is even more important to study the histopathology of natural ASF infection in more depth (17, 18, 29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…WSL cells were cultivated in Iscove’s Modified Dulbecco’s Medium with Ham’s F-12 Nutrient Mix (Thermo Fisher Scientific, Waltham, MA, USA): 10% FBS, 1% penicillin, and streptomycin (10,000 U/mL; Gibco, Thermo Fisher Scientific, Waltham, MA, USA). Virus isolation and titration on porcine macrophages were carried out with macrophages derived from peripheral blood mononuclear cells (PBMCs) as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%